1986
DOI: 10.1002/bip.360251204
|View full text |Cite
|
Sign up to set email alerts
|

Sol–sol structural transition of aqueous agarose systems

Abstract: SynopsisA structural transition is reported to occur in aqueous sols of agarose, an electrically uncharged biostructural polysaccharide. The transition has no measurable effect on size dispersity on the shape of the solute polysaccharide as observed by precision photon correlation spectroscopy. It originates a low-angle pattern of scattered light similar to that which monitors phase separations in polymer blends. Thus, it must be due to some extent to spatially modulated polymer clustering, typical of spinodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 53 publications
(6 reference statements)
9
41
0
Order By: Relevance
“…The gelation of aqueous agarose sols, its reversibility, and the molecular and supramolecular structure of the polysaccharide, as well as the structure of the surrounding water, have been the object of many studies [24,25,. These have shown that the underlying physics includes two concentration-dependent processes, both implying molecular recognition, i.e., a conformational transition from single strands to double helices and aggregation of double helical segments to form bundles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The gelation of aqueous agarose sols, its reversibility, and the molecular and supramolecular structure of the polysaccharide, as well as the structure of the surrounding water, have been the object of many studies [24,25,. These have shown that the underlying physics includes two concentration-dependent processes, both implying molecular recognition, i.e., a conformational transition from single strands to double helices and aggregation of double helical segments to form bundles.…”
Section: Methodsmentioning
confidence: 99%
“…Recent experiments have shown for the first time the role of spinodal decomposition in the promotion of functional encounters of solute biomolecules [24,25]. The specific case is that of agarose, a biopolysaccharide capable of self-assembling in a supramolecularly ordered gel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…25) The average pore diameter in agarose hydrogel depends on the amount of the geling agent, and the reported pore diameter ranges 200 to 500 nm. 26),27) The strength of the agarose hydrogel depends on the macromolecular network in the hydrogel.…”
Section: )4)mentioning
confidence: 99%